Marriage and its representations in Classical Hollywood Comedy (1934-1945). Stanley Cavell, the concept of skepticism and Kierkegaard's legacy Marriage and its representations in Classical Hollywood Comedy (1934-1945) - Toufic Ishaya El-Khoury (Journal for Religion, Film and Media, 2018)
This article explores the questions of marriage and divorce as discussed by Stanley Cavell in his study of Classical Hollywood comedies, dubbing what he considered as a popular subgenre of the American comedy of the thirties and forties: the "comedy of remarriage". We will focus on Cavell's analysis of a series of films, and the way these comedies belong to a specific American school of thought, with a case study of The Awful Truth (Leo McCarey, US 1937). We will then try to identify, in Cavell's original approach of marriage and divorce in the light of his discussion of philosophical skepticism, traces of Kierkegaard's moral legacy, by way of Wittgenstein's influence on the American thinker.